Analisis Pengaruh Struktur Modal, Dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Subsektor Non-Cylical - Dennis Stefanus; Anton Arisman (Universitas Multi Data Palembang, 2026)
This study analyzes the effect of capital structure and liquidity on profitability in non-cyclical subsector companies listed on the Indonesia Stock Exchange during 2022–2024. The study uses a quantitative approach with secondary data obtained from annual financial reports. Capital structure is measured by Debt to Equity Ratio (DER), liquidity by Current Ratio (CR), and profitability by Return on Assets (ROA). Panel data regression is applied to test the hypotheses. The results show that capital structure has a negative and significant effect on profitability, while liquidity has a positive and significant effect on profitability. These findings indicate that optimal debt management and adequate liquidity levels are important factors in improving company performance. The study contributes to financial management literature and provides practical implications for managers and investors.